1988
DOI: 10.1172/jci113778
|View full text |Cite
|
Sign up to set email alerts
|

Depression of systolic and diastolic myocardial reserve during atrial pacing tachycardia in patients with dilated cardiomyopathy.

Abstract: Previous reports have shown that increases in heart rate may result in enhanced left ventricular (LV) systolic and diastolic performance. To assess whether this phenomenon occurs in the presence of depressed LV function, the effects of pacing on LV pressure and volume were compared in seven patients with dilated cardiomyopathy (LV ejection fraction 0.19+0.11) and six patients with no or minimal coronary artery disease (LV ejection fraction 0.69±0.11). Patients with normal LV function demonstrated significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(60 citation statements)
references
References 32 publications
2
56
0
2
Order By: Relevance
“…Depressed cardiac contractility and impaired relaxation are key abnormalities contributing to morbidity and mortality in clinical HF (5,18). Despite the fact that numerous studies from both human (3,24) and animal (2, 22, 36) models of HF have attributed the mechanical dysfunction to changes in the calcium regulation observed in isolated myocytes (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…Depressed cardiac contractility and impaired relaxation are key abnormalities contributing to morbidity and mortality in clinical HF (5,18). Despite the fact that numerous studies from both human (3,24) and animal (2, 22, 36) models of HF have attributed the mechanical dysfunction to changes in the calcium regulation observed in isolated myocytes (see Refs.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34] Nevertheless, Sinha et al reported no adverse effects of long-term overdrive atrial pacing in patients with SA and HF. 22 In our study, mean nocturnal heart rate during OVP was of 71 ± 8 bpm with 96% ± 6% of ventricular pacing.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reduced myocardial functional reserve during atrial pacing tachycardia or during dobutamine stress test is reportedly caused by the impairment of intracellular calcium handling, especially of SERCA2 or phospholamban (35)(36)(37) in the failing heart; and that is related to the poor prognosis (11,38 Fig. 1 and 2).…”
Section: Sympathetic Nerve Functional Imaging With 123 I-mibgmentioning
confidence: 99%